ANALISIS HIDROLOGI DATA CURAH HUJAN SATELIT DAS BATANG SIANOK SEBAGAI PREDIKSI POTENSI BANJIR - Armanda, Rofik; Andrea Sumarah Asih (Retii, 2024)
This study analyzes 25 years of rainfall data (2000-2024) in the Batang Sianok Watershed (DAS), West Sumatra, using satellite data from Giovanni NASA. The Log Pearson Type III frequency analysis is applied to identify the rainfall distribution pattern, while the Nakayasu Synthetic Unit Hydrograph (HSS) is used to model the watershed's hydrological response to planned rainfall for various return periods. The results show a flood discharge of Q 1234 mÂ³/s for a 10-year return period, with the potential to trigger major flooding in the Batang Sianok watershed. The hydrograph modeling generates peak discharge predictions that are relevant to support flood risk mitigation and water resource management planning in the area.